Characteristics of Sudden Death Cases in The Medical Forensic and Medicolegal Installation in RSUD DR. Moewardi from 2017-2022 - Priyambodo, Dewanto Yusuf; Afidah, Nuraini Salma; Tri Artanti, Martiana Suciningtyas (Universitas Ahmad Dahlan, 2024)
Sudden death represents a significant global health burden that can affect any population. The potential for sudden death to affect any individual at any time underscores the importance of investigating this issue. The findings of this study may serve to reinforce existing evidence regarding sudden death, thereby facilitating the implementation of additional measures in a timely and appropriate manner. The objective of this study is to determine the prevalence of sudden death cases in RSUD dr. Moewardi from 2017 to 2022, identify the socio-demographic profile of the most vulnerable population groups, and ascertain the most predominant system of involvement. Research was conducted with descriptive observational study, cross-sectional design, and purposive sampling. Subject consists of sudden death cases in the Medical Forensic and Medico Legal Installation in RSUD dr. Moewardi from 2017 to 2022. Of the 100 cases, the highest number was observed in 2020, representing 29% of the total cases. Individuals in the pre-elderly age group (39%) and male gender (88%) are most likely to experience sudden death. The primary cause of suspected sudden death is of other systems involvement (57.3%), with the cardiovascular system (54.54%) being the most common cause of sudden death. Sense-related abnormalities are the predominant indicator of past comorbidities in both suspected (56.17%) and sudden death cases (72.72%). The author concluded that pre-elderly male individuals are the most vulnerable to sudden death. The primary cause of suspected sudden death is of the other systems of involvement and the cardiovascular system in sudden death, with sense organ abnormalities being the predominant comorbidity indicator in both instances.